Diet, Feed Preferences, and Nutritional Intake of Hylobates albibarbis in Transit Cage BKSDA Kalimantan Tengah - Adisty Virakawugi Darniwa; Ida Kinasih; Nurul Aulia Fitri (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2023)
AbstractHylobates albibarbis is a type of small primate that lives on the island of Borneo with a characteristic black face and white hair on the eyebrows, cheeks, and chin that resembles a beard. H. albibarbis feeding management is important in conservation efforts on ex-situ conservation because of animal welfare. This study aims to determine the composition of the diet, feed preferences and nutritional intake of feed given to H. albibarbis in transit cage at the Palangka Raya-Central Kalimantan Office for Conservation of Natural Resources (named Balai Konservasi Sumber Daya Alam-BKSDA) under the Directorate of Conservation of Natural Resources and Ecosystems of the Ministry of Environment & Forestry of the Republic of Indonesia. The methods used are focal animal sampling and restricted feeding observed in individual male adult and infant of H. albibarbis. The observations show that the feed preferred by adult H. albibarbis was the Ambon banana (98.21%) and the least preferred was the Kepok banana (74.26%). Otherwise, in infants H. albibarbis the most preferred feed was papaya (93.43%), and the least preferred feed was Ambon banana (58.10%). The average daily feed intake for adult H. albibarbis was 658.52 g, and for infant was 378.16 g. H. albibarbis in transit cage at the Palangka Raya BKSDA office, Central Kalimantan had good growth and healthy physical condition assumed from their body weight and length.AbstrakHylobates albibarbis merupakan kera kecil yang hidup di Pulau Kalimantan dengan ciri khas wajah berwarna hitam dan rambut berwarna putih pada alis, pipi, dan dagu yang menyerupai janggut. Pengelolaan pakan H. albibarbis penting dalam upaya konservasi dengan konservasi ex-situ untuk kesejahteraan hewan. Penelitian ini bertujuan untuk mengetahui komposisi pakan, preferensi pakan, dan asupan nutrisi pakan yang diberikan pada H. albibarbis di kandang transit kantor BKSDA Palangka Raya Kalimantan Tengah. Metode yang digunakan adalah focal animal sampling dan restricted feeding pada individu jantan dewasa dan jantan bayi H. albibarbis. Observasi dilakukan dalam durasi 12 jam selama 31 hari. Hasil pengamatan menunjukkan bahwa pakan yang disukai H. albibarbis dewasa adalah pisang Ambon (98,21%) dan yang tidak disukai adalah pisang Kepok (74,26%). Pakan yang disukai bayi H. albibarbis adalah pepaya (93,43%) dan yang tidak disukai adalah pisang Ambon (58,10%). Total asupan pakan harian untuk H. albibarbis dewasa adalah 658,52 g. Total asupan pakan harian untuk H. albibarbis bayi adalah 378,16 g. H. albibarbis di kandang transit kantor BKSDA Palangka Raya Kalimantan Tengah memiliki pertumbuhan yang baik dan kondisi fisik yang sehat berdasarkan berat badan dan panjang tubuhnya.